2019
DOI: 10.1073/pnas.1908180116
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq identifies a reversible mesodermal activation in abnormally specified epithelia of p63 EEC syndrome

Abstract: Mutations in transcription factor p63 are associated with developmental disorders that manifest defects in stratified epithelia including the epidermis. The underlying cellular and molecular mechanism is however not yet understood. We established an epidermal commitment model using human induced pluripotent stem cells (iPSCs) and characterized differentiation defects of iPSCs derived from ectrodactyly, ectodermal dysplasia, and cleft lip/palate (EEC) syndrome patients carrying p63 mutations. Transcriptome anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 44 publications
(81 reference statements)
0
26
0
Order By: Relevance
“…This suggests that TP63 or ΔNp63 is dispensable for epidermal lineage commitment. Intriguingly, introducing p63 mutants from EEC patients into induced pluripotent stem cells (iPSCs) dramatically impairs the induction of epidermal marker K14 in an epidermal commitment model [ 58 ] induced by retinoic acid (RA) and bone morphogenetic protein 4 (BMP4) [ 59 ], arguing that TP63 is essential for epidermal commitment. These opposite interpretations may indicate that other lineage-determining factors could compensate for p63 function in a p63-null context, whereas mutant p63 in iPSCs abrogates the function of the normal p63.…”
Section: Tp63 In Epidermal Commitment and Differentiationmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that TP63 or ΔNp63 is dispensable for epidermal lineage commitment. Intriguingly, introducing p63 mutants from EEC patients into induced pluripotent stem cells (iPSCs) dramatically impairs the induction of epidermal marker K14 in an epidermal commitment model [ 58 ] induced by retinoic acid (RA) and bone morphogenetic protein 4 (BMP4) [ 59 ], arguing that TP63 is essential for epidermal commitment. These opposite interpretations may indicate that other lineage-determining factors could compensate for p63 function in a p63-null context, whereas mutant p63 in iPSCs abrogates the function of the normal p63.…”
Section: Tp63 In Epidermal Commitment and Differentiationmentioning
confidence: 99%
“…It has been shown that genes expressed at an early differentiation stage are not under the control of p63. The p63 protein predominantly regulates genes during the specification switch from the multipotent state to the epidermal fate [ 59 ]. Thus, these studies suggest that p63 plays a prominent role in maturation, rather than the initiation stage of skin differentiation triggered by inductive morphogens (Table 1 ).…”
Section: Tp63 In Epidermal Commitment and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from numerous studies have demonstrated that p63, a homolog of p53, is vital for the normal development and homeostasis of epithelial tissues, in both humans and mice. For instance, heterozygous mutations in human p63 drives several developmental defects and disorders, especially skin abnormalities (47)(48)(49). In animal studies, p63 knockout led to severe anomalies in the development of epithelia and their derivatives, and even death at birth (25,50).…”
Section: Discussionmentioning
confidence: 99%